Belonging and Globalisation: Critical Essays in Contemporary Art & Culture - Boullata, Kamal; Al Qasimi, Hoor; Bohrer, Frederick N.; Boullata, Kamal; Bourriaud, Nicolas; Brollo, Boris; Dos Santos, Laymert Garcia; Fisher, Jean; Khoury, Elias; Lum, Ken; Massad, Joseph; Mattawa, Khaled; et al. (London; Saqi Books, 2008)
Compilation of essays that bring together voices that are involved in shaping the art and cultural scenes outside of the Western mainstream. All essays originally appeared in the catalogue for SB7. Contributors: Hoor Al Qasimi, Frederick N. Bohrer, Kamal Boullata, Nicolas Bourriaud, Boris Brollo, Jean Fisher, Laymert Garcia Dos Santos, Elias Khoury, Ken Lum, Joseph Massad, Khaled Mattawa, Gerardo Mosquera, Achille Bonito Oliva, Jack Persekian, Nadia Tazi and Tirdad Zolghadr
English
Keywords: N61-72 Theory. Philosophy. Aesthetics of the visual arts